Vertically Transferred Immunity in Neonates: Mothers, Mechanisms and Mediators - Albrecht, Marie; Arck, Petra Clara (Frontiers in Immunology, 2020)
Over the last years, an increasing number of outbreaks of vaccine-preventable infectious diseases has been reported. Besides elderly and immunocompromised individuals, newborns and small infants are most susceptible to infections, as their immune system is still immature. This vulnerability during infancy can be mitigated by the transplacental transfer of pathogen-specific antibodies and other me-diators of immunity from mother to the fetus during pregnancy, followed postnatally by breast milk-mediated immunity. Since this largely antibody-mediated passive immunity can prevent the newborn from infections, neonatal immunity depends strongly on the maternal concentration of respective specific antibodies during pregnancy. If titers are low or wane rapidly after birth, the protection trans-ferred to the child may not be sufficient to prevent disease. Moreover, emerging concepts propose that mothers may transfer active immunity to the newborns via vertical transfer of pathogen-specific T cells. Overall, a promising strategy to augment and prolong neonatal immunity is to vaccinate the mother before or during pregnancy in order to boost maternal antibody concentrations or availability of specific T cells. Hence, a large number of pre-and postconceptional vaccine trials have been carried out to test and confirm this concept. We here highlight novel insights arising from recent research endeavors on the influence of prenatal maternal vaccination against pathogens that can pose a threat for newborns, such as measles, pertussis, rubella and influenza A. We delineate pathways involved in the transfer of specific maternal antibodies. We also discuss the consequences for children’s health and long-term immunity resulting from an adjustment of prenatal vaccination regimes.